PENGARUH IKLIM SEKOLAH, KREATIVITAS, DAN PENGALAMAN MENGAJAR TERHADAP MUTU PEMBELAJARAN GURU PADA SEKOLAH DASAR SE KECAMATAN KARANGSAMBUNG KABUPATEN KEBUMEN (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims to describe: (1) the extent of the influence of school climate, creativity and teaching experience simultaneous to the quality of learning in elementary schools on Karangsambung districts Kebumen regency, (2) the extent of the influence of school climate partially on the quality of learning on elementary schools at districts Karangsambung Kebumen regency, (3) the extent of the influence of creativity partially on the quality of learning on elementary schools at districts Karangsambung Kebumen regency,and (4) the extent of the influence of teaching experience partially on the quality of learning on elementary schools at districts Karangsambung Kebumen regency.This study was conducted in an elementary school as the District Karangsambung Kebumen regency. The population was elementary school teachers as the District Karangsambung Kebumen regency. Total population of 174 teachers. The sampling technique used is proportionale random sampling technique. The total sample of 125 teachers. Technique data collection using questionnaires. Analysis using Multiple Regression Analysis and Partial Correlation.Based on the results of this study concluded: (1) there is a significant positive effect of school climate, creativity and teaching experience simultaneous to the quality of learning teachers in elementary schools on Karangsambung districts Kebumen regency. This means if the variables increases, the quality of learning teachers will also increase. (2) there is a significant positive effect of school climate partially on the quality of learning on elementary schools at districts Karangsambung Kebumen regency. It Means if the school climate more conducive, then the quality of teacher learning is increasing. (3) there is a significant positive influence of creativity partially on the quality of learning on elementary schools at districts Karangsambung Kebumen regency. It means if the creativity of the teacher, the better the quality of learning of teachers is increasing, and (4) there is a significant positive effect of teaching experience partially on the quality of learning on elementary schools at districts Karangsambung Kebumen regency. It means if the experience of teachers of teachers is increasing then the quality of learning is increasing